At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
turn it into exponent form, so Log(1/6)36 ⇒ (1/6)^x=36
1. 6²=36
2. (1/6)²=(1²/6²)=1/36
so Log(1/6)36=2
:) hope that helped...
1. 6²=36
2. (1/6)²=(1²/6²)=1/36
so Log(1/6)36=2
:) hope that helped...
Answer:
[tex]\text{log}_{\frac{1}{6}}(36)=-2[/tex]
Step-by-step explanation:
We have been given a logarithm expression [tex]\text{log}_{\frac{1}{6}}(36)[/tex]. We are asked to evaluate our given expression.
Using logarithm rule [tex]log_{\frac{1}{a}}(x)=-log_a(x)[/tex], we can write our expression as:
[tex]\text{log}_{\frac{1}{6}}(36)=-\text{log}_6(36)[/tex]
[tex]\text{log}_{\frac{1}{6}}(36)=-\text{log}_6(6^2)[/tex]
Using logarithm rule [tex]\text{log}_{a}(x^b)=b\text{log}_a(x)[/tex], we will get:
[tex]\text{log}_{\frac{1}{6}}(36)=-2\text{log}_6(6)[/tex]
Applying rule [tex]\text{log}_{a}(a)=1[/tex], we will get:
[tex]\text{log}_{\frac{1}{6}}(36)=-2\cdot 1[/tex]
[tex]\text{log}_{\frac{1}{6}}(36)=-2[/tex]
Therefore, [tex]\text{log}_{\frac{1}{6}}(36)=-2[/tex].
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.